THE LEGAL REFORM OF THE WAQF LAW RESOLUTION BASED ON PANCASILA - Islamiyati Islamiyati; Ahmad Rofiq; Ro’fah Setyowati; Dewi Padusi Daengmuri (Diponegoro Law Review, 2019)
Nowadays, there are still some shortages in the rule of law of the waqf disputes resolution, therefore a lot of waqf disputes have not be solved, and moreover it has no justice value since it does not protect the rights of disputing parties. Why the legal renewal of  waqf disputes resolution based on Pancasila is important? The urgency is as the media for the enforcement and the law enactment of  the waqf dispute resolution based on Pancasila. This research is field research, and the approach method is juridical empirical. The result of the research is to explain that the legal reform of waqf dispute resolution is important because the waqf disputes always develope based on the socio-cultural development of the society. Besides, it also saves the waqf assets, gives the values of justice and certainty,makes  the rule of the law not rigid and closed, can finish the waqf disputes, and makes waqf  meaningful in the society. The legal reform  of waqf disputes resolution which is based on Pancasila means making the policy that includes determining and deciding the rules of waqf dispute resolution, hence it will be suitable with the direction of national development based on Pancasila.